Answer:
x = -16
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Explanation:
Step 1: Define Equation
10(1/2x + 2) - 5 = 3(x - 6) + 1
Step 2: Solve for x
- Distribute: 5x + 20 - 5 = 3x - 18 + 1
- Combine like terms: 5x + 15 = 3x - 17
- Subtract 3x on both sides: 2x + 15 = -17
- Subtract 15 on both sides: 2x = -32
- Divide 2 on both sides: x = -16
Step 3: Check
Plug in x into the original equation to verify it's a solution.
- Substitute in x: 10(1/2(-16) + 2) - 5 = 3(-16 - 6) + 1
- Multiply: 10(-8 + 2) - 5 = 3(-16 - 6) + 1
- Add/Subtract: 10(-6) - 5 = 3(-22) + 1
- Multiply: -60 - 5 = -66 + 1
- Subtract/Add: -65 = -65
Here we see that -65 does indeed equal -65.
∴ x = -16 is the solution of the equation.